2022
DOI: 10.3390/life12040571
|View full text |Cite
|
Sign up to set email alerts
|

The Palliative Care in the Metastatic Spinal Tumors. A Systematic Review on the Radiotherapy and Surgical Perspective

Abstract: Spine represents the most common site for metastatic disease involvement. Due to the close relationship between the spinal cord and critical structures, therapeutical management of metastatic spinal cord disease remains challenging. Spinal localization can lead to neurological sequelae, which can significantly affect the quality of life in patients with a limited life expectancy. The authors conducted a systematic literature review according to PRISMA guidelines in order to determine the impact of the most upd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…Metastatic spine disease management remains a palliative approach. Nonetheless, medical and surgical care are cardinal in ameliorating pain and improving quality of life in such patients [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic spine disease management remains a palliative approach. Nonetheless, medical and surgical care are cardinal in ameliorating pain and improving quality of life in such patients [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spine is one of the most common sites for the involvement of metastatic disease (8,9). As an advanced stage of cancer, metastatic spinal disease is often characterized by severe back pain, infection, neurological sequelae, and ambulatory disability (8), which are particularly challenging for surgeons. Of note, patients with spine metastasis have been proved to be relevant to declined life expectancy (8) and poor quality of life (10)(11)(12) because of above complications.…”
Section: Introductionmentioning
confidence: 99%
“…As an advanced stage of cancer, metastatic spinal disease is often characterized by severe back pain, infection, neurological sequelae, and ambulatory disability (8), which are particularly challenging for surgeons. Of note, patients with spine metastasis have been proved to be relevant to declined life expectancy (8) and poor quality of life (10)(11)(12) because of above complications. Studies have demonstrated that surgical interventions could be capable of improving the quality of patient's remaining life due to immediate pain relief and functional recovery among patients with spine metastasis (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spine metastases are a severe consequence of cancer patients, and the incidence of spine metastases has significantly increased due to growing cancer patients and prolonged life expectancy among those patients [2]. This disease is featured by intractable severe back pain, neurological sequelae, and even incontinence and disability, all of which could have a significant impact on the quality of life among patients with a limited life expectancy [3]. Thus, maintaining or promoting the patient's quality of life to the greatest extent possible is the primary objective of contemporary treatment for spinal metastases.…”
Section: Introductionmentioning
confidence: 99%